White female experiences of the Zimbabwean liberation war: Patricia Charter’s Crossing the boundary fence, Sylivia Bond Smith’s Ginette, Partridge’s To breathe and wait. - Mutongwizo, Tanyaradzwa Dianah (Midlands State University, 2014)
This study explores the experiences of white females in Rhodesia during the liberation war. For this purpose, Particia Chater’s Crossing the Boundary Fence (1991), Sylvia Bond Smith’s Ginette (1980) and Nancy Partridge’s To Breathe and Wait (1986) have been selected as they fit in well in the context of experiences faced by white women during the liberation war.